Malware, Data Theft and Emotional Distress as Risk Factors of Phishing in Nigeria - Adeyemo , Lateef Junior; David, Isaiah Oden; Olabulo, Tirimisiyu Yemi (International Journal of Criminology & Justice, 2025)
This study investigates malware, data theft, and emotional distress as risk factors contributing to phishing vulnerability among Nigerian internet users. Data were collected from 2,016 participants through purposive and convenience sampling, using a quantitative cross-sectional survey design. The analyses focused on platform exposure, behavioural patterns, and sociodemographic predictors of emotional reactions to phishing incidents. Findings revealed that phishing threats vary across social media, with Instagram, Twitter, and Facebook being most affected. Emotional distress is highest when users experience real consequences, while overconfidence and exposure fatigue reduce vigilance. Sociodemographic factors such as age, gender, education, and occupation significantly predict emotional reactions to attacks. It is therefore recommended that phishing prevention in Nigeria requires joint efforts from various agencies, associations, and the Ministry of Health to implement cybersecurity education, block threats in real time, train self-employed users, provide emotional support, and involve technology companies in user protection through reporting systems, safety tools, and targeted awareness initiatives.